The meaning of modern neuroanatomy - Andrzej Żytkowski; Stanisław Orkisz (Elsevier, 2024)
Background: Neuroanatomy, the study of the structure and organization of the nervous system, has developed gradually to become a cornerstone of neurological sciences. As understanding of the brain and its intricate networks continues to evolve, modern neuroanatomy integrates advanced technologies and multidisciplinary approaches to provide deeper insights into the complexities of the human brain. Aim: This report aims to present the meaning of modern neuroanatomy, its tools, applications, and the future perspectives. Conclusions: The data gained from modern neuroanatomy have profound implications for understanding brain function, diagnosing and treating neurological disorders, and addressing ethical and societal challenges.